Factors affecting the decision making in off farm employment among paddy farmers in Kemasin Semerak - Man, Norsida (Universiti Putra Malaysia Press, 2009)
Poverty is one of the most serious problems confronting paddy farmers worldwide, and Malaysia is not an exception. Off farm employment is an alternative strategy and it has a potential to improve the income and well-being of the paddy farmers. This study assessed the off-farm employment decision among 250 paddy farmers in Kemasin Semerak granary area. In specific, the study attempted to determine the relationship between the determinants of the off-farm and the off-farm participation decision. It was also undertaken to describe the characteristics of respondents and their status in the off-farm employment. Furthermore, it examined the income level of the farm households from the paddy farming and the off-farm employments as well as showed the effects of the off-farm employment to the paddy farmers, using the descriptive analysis and logit regression methods. The variables which were found to influence the likelihood of the paddy farmers to be engaged in the off-farm employment included the farmers’ age and gender, the number of dependants, as well as other income and farming types. From the study, it was evident that the farm size and education were not significant factors as no significant association was observed between them and the off-farm participation.